Classification and Radiological Diagnosis of Thoracolumbar Spine Fractures: WFNS Spine Committee Recommendations - Abdul Hafid Bajamal; Khrisna Rangga Permana; Muhammad Faris; Mehmet Zileli; Nikolay A. Peev (Neurospine, 2021)
The aim of this review to determine recommendations for classification and radiological diagnosis of thoracolumbar spine fractures. Recommendation was made through a literature review of the last 10 years. The statements created by the authors were discussed and voted on during 2 consensus meetings organized by the WFNS (World Federation Neurosurgical Societies) Spine Committee. The literature review was yielded 256 abstracts, of which 32 were chosen for full-text analysis. Thirteen papers evaluated the reliability of a classification system by our expert members and were also chosen in this guideline analysis. This literature review-based recommendation provides the classification and radiologic diagnosis in thoracolumbar spine fractures that can elucidate the management decision-making in clinical practice.